LITERATURE REVIEW: EFEK LATIHAN FIFA 11+ TERHADAP PENINGKATAN DYNAMIC POSTURAL CONTROL PADA PEMAIN SEPAK BOLA - Alma Dinastri, (2021)
Objective: The warm-up method recommended by the Federation of International Football Association is FIFA 11+ Which consists of training sections, namely running exercise, strength plyometric-balance, and running exercise in which there are 15 movement. This study aims to determine the Effects of FIFA 11+ Training on Increasing Dynamic Postural Control in Football Players. Method: The research method used is a literature review, to search for literature sources using several keyboard in the 2016-2021 range. From the results of the literature search, there were 4 articles and journal that met the source inclusion criteria. As well as the assessment of methodological quality and 4 journallism is assessed using the scimago journal & country rank (SJR). Results: After analyzing 4 journals, it was found that there was an increase in Dynamic Postural Control. Conclusion: There is an increase in Dynamic Postural Control with FIFA 11+ training.